Small cell carcinoma with neuroendocrine differentiation of subglottic larynx- a case report - Becht, Rafał; Kiełbowski, Kajetan; Żychowska, Justyna; Dembowska, Wiktoria; Król, Małgorzata; Birkenfeld, Bożena; Owsiak, Mateusz; Lewandowska, Magdalena; Kubrak, Jadwiga; Amernik, Katarzyna (Frontiers in Oncology, 2023)
Small cell cancer (SCC) is a neuroendocrine neoplasm, which is most frequently found in the lungs. Extrapulmonary location of SCC is rare and may involve 2.5-5% of SCCs. We present a case of a 31-year-old male patient with an extremely uncommon subglottic SCC. The patient was qualified for a radical sequential chemoradiotherapy. After treatment, patient's condition suggested complete remission. Recurrence was detected one year later, and the disease rapidly progressed, despite a second line chemotherapy. The patient died 29 months after initial diagnosis. This case aims to raise awareness 2 This is a provisional file, not the final typeset article on the aggressive laryngeal SCC and its good response to first line chemotherapy composed of cisplatin and etoposide, followed by radiotherapy.